Analysis of CDM Projects' Portfolio in West African Economic and Monetary Union - Regional Baseline Assessment in Energy Sector. Case Study: Benin, Burkina Faso, Niger and Togo - Honorat Satoguina (Hamburg Institute of International Economics (HWWA), 2006)
This study analyses current energy projects in Benin, Burkina Faso, Niger and Togo. Based on the size of these projects, the study shows that currently, only small scale CDM projects can be developed in these countries in energy sectors. Moreover, baseline emissions factors are assessed for the different electricity grids. These baselines are very low in interconnected grids in cities, while they are relatively high for isolated and non-connected utilities in remote areas. Consequently, countries can maximise their revenues through CDM projects in remote areas. Given that electricity exchange occurs between countries of the West African Economic and Monetary Union (WAEMU) and other West African countries, the assessment of regional baseline emissions factors shows very low emissions factors, due to the high hydro electricity import in Benin, Togo and Niger. However, the result is different in Burkina Faso, which imports less hydro electricity comparatively. The study therefore suggests that small countries with suppressed demand are exempted from the use of the regional baseline emissions.
Keywords: G11; D00; Q20; G20; 330; Energy projects; CDM projects; regional baseline